Upaya Meningkatkan Keterampilan Berbahasa Indonesia Dengan Menumbuhkan Minat Membaca Melalui Pemodelan Pada Siswa Kelas I SD Negeri 060886 Medan Tahub Ajaran 2017/2018 - Agustina Ginting (Keguruan, 2022)
The proposed hypothesis is: How is the activeness and ability to read in Indonesian subjects for Class I students in SD Negeri 060886 Medan 2017/2018 academic year. This classroom action research was conducted in two cycles by using Kurt Lewin's model that consists of four components, namely: planning, action/action, observation and reflection. The results of the study concluded that student learning outcomes in reading in Indonesian subjects were: The average value of student interest when working on LKS in the Pre-Cycle was 47.83; then in the 1st cycle increased into 67.83 and then increased again to 97.39 in the 2nd cycle. The average value of student interest at the time of LKS Discussion in the Pre-Cycle is 42.61; then in the 1st cycle increased into 72.17 and then increased again into 93.91 in the 2nd cycle. The average value of students' interest during the discussion in the Pre-Cycle is 44.35; then in the 1st cycle increased into 74.78 and then increased again into 92.17 in the 2nd cycle. The average value of student interest at the time of evaluation in the pre-cycle is 45.22; then in the 1st cycle increased into 73.04 and then increased into 96.52 in the 2nd cycle. The average value of the learning evaluation results in the pre-cycle is 62.61; then in the 1st cycle increased into 72.68 and then increased into 92.03 in the 2nd cycle. According the results, it can be concluded that growing interest in reading can improve the Indonesian language skills toward the class I SD Negeri 060886 Medan.